Super Car Rental Enterprise: car rental services / Nursyahril Nadya Azmi ...[et al.] - Azmi, Nursyahril Nadya; P. Mastar, Norshila; Mohamed Noh, Noraniza; Amir, Nor Fazerah; Puchot, Nur Asyikin (2013)
We came to a conclusion after we conducted an extensive research on the available business all over the country; we have agreed to start a company which makes car rental services.